Six new species of Archimonocelididae Meixner, 1938 (Platyhelminthes, Proseriata) from the Pacific, with proposal of a new genus - Curini-Galletti, Marco; Schockaert, Ernest R. (Zootaxa, 2021)
The genus Tajikacelis n. gen. is introduced for species of Archimonocelididae (Proseriata) characterized by the lack of atrial spines in the copulatory organ and by the opening of the seminal vesicles into the prostate vesicle at its ventral side. Six new species from the Pacific Ocean are ascribed to the new genus; they may be distinguished by features of the genital systems and the morphology of their copulatory stylets. T. tajikai n. sp. (type species of the new genus) and T. macrostomoides n. sp., both from eastern Australia, have a long tubular stylet. In T. macrostomoides n. sp., the stylet is more curved, bending to 180°, and has a narrower basis compared to that of T. tajikai n. sp. In T. artoisi n. sp., from Hawai’i, and T. nematoplanoides n. sp., from South Australia, the stylet is shaped as a truncated cone, with a broad, oblique proximal opening and a very short tubular part. T. artoisi n. sp. is distinct for the much stronger thickening of the dorsal side of the stylet, and for the different shape of the proximal opening. In T. acuta n. sp. and T. truncata n. sp., from West Panama, the tubular stylet is comparatively short; the two species differ for the shape of the distal opening, produced into a sharp spike in T. acuta n. sp., and square-ended in T. truncata n. sp.. Two species previously described in the genus Archimonocelis are transferred to Tajikacelis n. gen.: T. itoi Tajika, 1981 from Japan and T. keke Martens and Curini-Galletti, 1989 from Sulawesi (Indonesia). The taxonomic position of the problematic Archimonocelis glabrodorsata Martens and Curini-Galletti, 1989 from the Caribbean is discussed. The relationships of and within the genus Tajikacelis n. gen. are discussed and compared with recent results based on DNA studies.